Remission and Incidence of Obstructive Sleep Apnea from Middle Childhood to Late Adolescence - Spilsbury, James C. (Sleep, 2015)
STUDY OBJECTIVE: To study the incidence, remission, and prediction of obstructive sleep apnea (OSA) from middle childhood to late adolescence. DESIGN: Longitudinal analysis. SETTING: The Cleveland Children's Sleep and Health Study, an ethnically mixed, urban, community-based cohort, followed 8 y. PARTICIPANTS: There were 490 participants with overnight polysomnography data available at ages 8–11 and 16–19 y. MEASUREMENTS AND RESULTS: Baseline participant characteristics and health history were ascertained from parent report and US census data. OSA was defined as an obstructive apnea- hypopnea index ≥ 5 or an obstructive apnea index ≥ 1. OSA prevalence was approximately 4% at each examination, but OSA largely did not persist from middle childhood to late adolescence. Habitual snoring and obesity predicted OSA in cross-sectional analyses at each time point. Residence in a disadvantaged neighborhood, African-American race, and premature birth also predicted OSA in middle childhood, whereas male sex, high body mass index, and history of tonsillectomy or adenoidectomy were risk factors among adolescents. Obesity, but not habitual snoring, in middle childhood predicted adolescent OSA. CONCLUSIONS: Because OSA in middle childhood usually remitted by adolescence and most adolescent cases were incident cases, criteria other than concern alone over OSA persistence or incidence should be used when making treatment decisions for pediatric OSA. Moreover, OSA's distinct risk factors at each time point underscore the need for alternative risk-factor assessments across pediatric ages. The greater importance of middle childhood obesity compared to snoring in predicting adolescent OSA provides support for screening, preventing, and treating obesity in childhood. CITATION: Spilsbury JC, Storfer-Isser A, Rosen CL, Redline S. Remission and incidence of obstructive sleep apnea from middle childhood to late adolescence. SLEEP 2015;38(1):23–29.